2018
DOI: 10.1155/2018/9328317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nd3+ Ion Concentration on the Corrosion Resistance of API X70 Steel in Chloride‐Rich Environments

Abstract: In this study, the effect of the addition of Nd 3+ ions as a corrosion inhibitor of the API X70 steel in a medium rich in chlorides was evaluated. e performance of the Nd 3+ ions was evaluated by means of electrochemical techniques such as potentiodynamic polarization curves, open circuit potential measurements, linear polarization resistance, and electrochemical impedance spectroscopy, as well as by means of scanning electron microscopy and EDS measurements. e results showed that Nd 3+ ions reduce the corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 37 publications
(49 reference statements)
4
17
0
1
Order By: Relevance
“…Electrochemical Evaluation. In order to compare the performance of the inhibitor synthesized from permanent magnets, its electrochemical evaluation was carried out in the same way as described by the authors in a previous work where neodymium chloride (analytical reagent, AR) was used as a corrosion inhibitor [24].…”
Section: Synthesis Of Corrosion Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical Evaluation. In order to compare the performance of the inhibitor synthesized from permanent magnets, its electrochemical evaluation was carried out in the same way as described by the authors in a previous work where neodymium chloride (analytical reagent, AR) was used as a corrosion inhibitor [24].…”
Section: Synthesis Of Corrosion Inhibitormentioning
confidence: 99%
“…However, despite the fact that most studies have focused on compounds based on Ce and La [17][18][19][20][21][22][23], the use of neodymium salts can also be an alternative to mitigate the corrosion problems. In a recent study, the authors have reported that neodymium chloride has excellent corrosion inhibition efficiency for API X70 steel immersed in a chloride-rich solution [24].…”
Section: Introductionmentioning
confidence: 99%
“…The observed changes allow inferring that the Figure 12: Equivalent circuit used to fit the impedance spectra. 8 International Journal of Polymer Science presence of the chitosan film decreases the dissolution rate of the carbon steel (increase in anodic slope), and due to the great displacement of the corrosion potential towards more active potentials (>200 mV), it acts as a cathodic coating affecting the oxygen reduction rate (cathodic reaction) and shifting the polarization curve to lower current densities [49]. The behavior of carbon steel coated with chitosan doped with nanoparticles is very similar to that observed in the presence of the undoped chitosan film.…”
Section: Electrochemical Evaluationmentioning
confidence: 99%
“…In the case of corrosion inhibitors, it has been suggested that when they cause a displacement in OCP values greater than ±85 mV, with respect to the blank, they can be defined as anodic or cathodic inhibitors depending on the direction of displacement [49,[54][55][56]. Therefore, in this case, it can be assumed that the deposited chitosan films act as cathodic coating based on the displacement caused in the OCP values with respect to bare carbon steel.…”
mentioning
confidence: 99%
See 1 more Smart Citation